Analysis Of Service Quality, Price And Container Distribution On Competitive Advantage Through Consumer Excellence At PT. Evergreen Shipping Agency Indonesia Makassar Branch - Hasniaty Hasniaty; Glorya Martzella Noija; Nasir Hamzah; Gunawan Bata Ilyas; Yohannes Johny Soetikno (International Journal of Artificial Intelligence Research, 2022)
This  research  was  conducted  at  PT.  Evergreen  Shipping  Agency  Indonesia Makassar branch as a container transportation and shipping company. The purpose of this study is to analyze the effect of service quality, price and distribution on competitive advantage through customer satisfaction. The population in this study are all consumers or exporters who use the services of PT Evergreen Shipping Agency Indonesia Makassar branch with saturated sampling or the entire population. The data collection instrument was in the form of a questionnaire distributed via google form, using quantitative analysis using the SmartPLS method. This study proposes ten (10) hypotheses, eight of which have a significant effect and three are not significant. The results of the study found (1) Service Quality has no significant effect on Consumer Satisfaction. (2) Price has a significant effect on Consumer Satisfaction, (3) Container Distribution has a significant effect on Consumer Satisfaction, (4) Consumer Satisfaction has no significant effect on Competitive Advantage, (5) Service Quality has no significant effect on Competitive Advantage, (6) Price has an effect significant effect on Competitive Advantage, (7) Container Distribution has a significant effect on Competitive Advantage, (8) Service Quality has no significant effect on Competitive Advantage through Consumer Satisfaction, (9) Price has a significant effect on Competitive Advantage through Consumer Satisfaction, (10) Container Distribution has an effect on significant impact on Competitive Advantage through Customer Satisfaction